Effect of Exercise Training on Peroxisome Proliferator-Activated Receptor [gamma] Level: A Systematic Review - Nazari, Maryam; Minasian, Vazgen; Sharifian, Mohammad Javad (Asian journal of sports medicine, 2024)
Context: Peroxisome proliferator-activated receptor [gamma] (PPAR-[gamma]) plays a crucial role in regulating oxidative phosphorylation and energy utilization, both of which are diminished in obesity and type 2 diabetes (T2DM), major risk factors for cardiovascular disease (CVD). It is well established that exercise, as one of the significant modifiable lifestyle factors, is associated with the expression and activity of PPAR-[gamma]-controlled genes. Evidence Acquisition: In this systematic review, we conducted comprehensive searches across various databases, including PubMed, ScienceDirect, and Google Scholar, for relevant literature published between January 2000 and May 2022. This study focused on published articles (in-vivo and human) in English. This review encompasses 16 studies (4 involving humans and 12 involving animals). Results: The findings from 14 studies indicated that various types of exercise programs, including regular exercise, resistance exercise, swimming, climbing, and treadmill running, effectively improved PPAR-[gamma] levels in individuals with T2DM, obese populations, and healthy subjects. Only two studies reported no significant improvement in PPAR-[gamma] levels following physical activity. Notably, all studies involving subjects with T2DM showed improved PPAR-[gamma] levels after exercise training. Conclusions: Upon comparing various types of exercise training, the collected data suggest that all forms of aerobic exercise, regardless of their type and duration, have the potential to up-regulate PPAR-[gamma] messenger ribonucleic acid (mRNA) expression. This study lays the foundation for further research into the association between different types of exercise training and PPAR-[gamma] levels/activity across various human populations. However, given the limited number of human studies, further high-quality research is necessary to draw firm conclusions. Keywords: Physical Exercise, Metabolism, Diabetes